Associations of five dietary indices with metabolic dysfunction-associated steatotic liver disease and liver fibrosis among the United States population - Xu, Min; Zhan, Yamei; Gao, Guohui; Zhu, Li; Wu, Tong; Xin, Guijie (Frontiers in Nutrition, 2024)
Background & Aims: The role of dietary factors in metabolic dysfunction-associated steatotic liver disease (MASLD)-which represents a new definition of liver steatosis and metabolic dysfunctionremains unclear. This study aimed to explore the relationships between dietary indices and MASLD. Methods: We analyzed data from the U.S. National Health and Nutrition Examination Survey (NHANES) 2017-2020 cycle, including 4,690 participants with complete vibration-controlled transient elastography (VCTE) data. Multivariate logistic regression models adjusted for covariates were used to assess the association between dietary indices, MASLD, and MASLD-associated liver fibrosis (MASLD-LF).Restricted cubic spline (RCS) models and subgroup analyses were also performed.Results: The Alternative Healthy Eating Index (AHEI), Healthy Eating Index-2020 (HEI-2020), Dietary Approaches to Stop Hypertension Index (DASHI), and Mediterranean Diet Index (MEDI) were found to be negatively associated with MASLD risk, while the Dietary Inflammatory Index (DII) had a positive association. The highest quartile of MEDI was linked to a 44% reduction in MASLD risk (Q1 vs Q4 odds ratio [OR]: 0.56; 95% confidence interval [CI]: 0.34-0.94, P for trend: 0.012). DASHI was uniquely associated with a reduced risk of MASLD-LF (continuous OR: 0.79; 95% CI: 0.64-0.97; P for trend: 0.003). Our RCS curves indicated a nonlinear association with DASHI-MASLD (p-overall: 0.0001, pnonlinear: 0.0066). Subgroup analyses showed robust associations among the non-Hispanic White and highly educated populations. Conclusion: Specific dietary patterns were associated with reduced risks of MASLD and MASLD-LF.The DASHI, in particular, showed a significant protective effect against MASLD-LF. These findings suggest potential dietary interventions for managing MASLD and MASLD-LF, although large-scale randomized controlled trials are warranted to validate these findings.